Modeling of Mechanical Stress Exerted by Cholesterol Crystallization on Atherosclerotic Plaques - Luo, Yuemei (2017)
Plaque rupture is the critical cause of cardiovascular thrombosis, but the detailed mechanisms are not fully understood. Recent studies have found abundant cholesterol crystals in ruptured plaques, and it has been proposed that the rapid expansion of cholesterol crystals in a limited space during crystallization may contribute to plaque rupture. To evaluate the effect of cholesterol crystal growth on atherosclerotic plaques, we modeled the expansion of cholesterol crystals during the crystallization process in the necrotic core and estimated the stress on the thin cap with different arrangements of cholesterol crystals. We developed a two-dimensional finite element method model of atherosclerotic plaques containing expanding cholesterol crystals and investigated the effect of the magnitude and distribution of crystallization on the peak circumferential stress born by the cap. Using micro-optical coherence tomography (μOCT), we extracted the cross-sectional geometric information of cholesterol crystals in human atherosclerotic aorta tissue ex vivo and applied the information to the model. The results demonstrate that (1) the peak circumference stress is proportionally dependent on the cholesterol crystal growth; (2) cholesterol crystals at the cap shoulder impose the highest peak circumference stress; and (3) spatial distributions of cholesterol crystals have a significant impact on the peak circumference stress: evenly distributed cholesterol crystals exert less peak circumferential stress on the cap than concentrated crystals.